THE ROLE AND IMPORTANCE OF MORAL VALUES IN SOCIETY (American Journal of Research in Humanities and Social Sciences, 2024)
In this article, moral values have a continuous history in world culture and history, and are based on the national punishment, men, and thinking of the Uzbek people.